2000
DOI: 10.1142/s0192415x00000489
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fasting on the Pulse Spectrum

Abstract: Nutrition is the major source of bioenergy. The present study investigated the physiological response to fasting by analyzing the effect of fasting on the pulse spectrum of the radial artery. Sixteen subjects were allowed to take only mineral water for 24 hours, and the pulse was measured at intervals during fasting and after eating resumed. Data were analyzed using one-way analysis of variance (ANOVA) with Scheffe's test for pairwise comparisons. The results indicate the second harmonic of the radial pulse in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Human and animal trials are being conducted to support this hypothesis (Young et al, 1989a;Young et al, 1989b;Young et al, 1992;Yu et al, 1994). Several scholars have applied this theory to investigate TCM physiology (Su et al, 2000;Wang et al, 1996b), Chinese herbs Wang et al, 2000;, formulae (Wang et al, 1998;Wang et al, 1995b;Wang et al, 1997), acupuncture (Wang et al, 1995a;Wang et al, 1996a), and clinical observation (Chen et al, 1993;Lu et al, 1999;Lu et al, 1996;Wang et al, 1996c). According to the previous studies, all evidence indicates that C0 is related to the heart, the 1st harmonic is related to the liver (and the liver meridian), the 2nd harmonic is related to the kidney (and the kidney meridian), the 3rd is related to the spleen, the 4th is related to the lung, and so on (Jan et al, 2003;Wang et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human and animal trials are being conducted to support this hypothesis (Young et al, 1989a;Young et al, 1989b;Young et al, 1992;Yu et al, 1994). Several scholars have applied this theory to investigate TCM physiology (Su et al, 2000;Wang et al, 1996b), Chinese herbs Wang et al, 2000;, formulae (Wang et al, 1998;Wang et al, 1995b;Wang et al, 1997), acupuncture (Wang et al, 1995a;Wang et al, 1996a), and clinical observation (Chen et al, 1993;Lu et al, 1999;Lu et al, 1996;Wang et al, 1996c). According to the previous studies, all evidence indicates that C0 is related to the heart, the 1st harmonic is related to the liver (and the liver meridian), the 2nd harmonic is related to the kidney (and the kidney meridian), the 3rd is related to the spleen, the 4th is related to the lung, and so on (Jan et al, 2003;Wang et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The theory provides the foundations for ACUTE HEMORRHAGE EFFECT ON PULSE SPECTRUM interpreting TCM by modern medical engineering. In 2001, Su et al (2000) conducted an experiment to explore what influence fasting could have on the human body in a physiological aspect. Through the use of pulse spectrum analysis, they found that the change of bio-energy against fasting always followed a certain pattern.…”
Section: Introductionmentioning
confidence: 99%
“…The time domain is widely used in cardiovascular research [22] and is also popularly used in the quantification of pulse condition [23]. Time domain analysis looks at the arterial pressure waveform with respect to time, and a time domain graph shows how the arterial pressure waveform changes over time.…”
Section: Time Domainmentioning
confidence: 99%
“…The majority of the studies that use the frequency domain to analyze the arterial pulse have focused on differentiating diseases [35][36][37], examining the power spectrum in relation to the meridians [38,39], and investigating the relationship among disease, syndrome, and channels [23,[40][41][42][43]45]. Only a few studies have explored the characteristics of the power spectrum for different pulse conditions [46,47].…”
Section: Frequency Domainmentioning
confidence: 99%
“…"Resonance of organs with the heart" provided a positive connection. Experiments (Wang et al, 1997;Young et al, 1989; and clinical studies (Chen et al, 1993;Su et al, 2000;Wan et al, 2000) have shown that the change in arterial pulse spectrum has a specific pattern, which enables clinicians to use such a spectrum as a quantitative probe. Thus, specific patterns of alteration in individual harmonic components can serve as physiological or pathological indicators under specific experimental/clinical conditions.…”
Section: Introductionmentioning
confidence: 99%